Diagnosis and prognosis of spontaneous pneumomediastinum in eighteen children - Zhang, Xue-ya (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2013)
OBJECTIVE: To analyze the diagnosis, treatment and prognosis of spontaneous pneumomediastinum (SPM) in children